Drivers of services sector growth acceleration in developing countries - Gideon Onyewuchi Ndubuisi; Solomon Owusu; Rexford Kweku Asiama; Elvis Korku Avenyo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The services sector is dominant and continues to experience unprecedented growth in many developing economies. However, in-depth empirical analysis of the drivers ofservicessector growth acceleration is limited. This paper examines and identifies the underlying factors that explain services sector growth accelerations and episodes in developing countries, and how these factors may differ across services types (market services and non-market services) and regions. Using the Economic Transformation Database for 50 developing countries for the period 1990- 2018 and applying probit estimation models, the authors identify several macro and institutional factors that are important drivers of market services sector growth acceleration. The results also suggest that there is a heterogeneous set of drivers that are key for total market services sector growth acceleration and non-market services sector growth acceleration. The paper concludes by discussing the policy implications of these emerging findings.
Keywords: L8; O14; O49; 330; services; services sector; economic growth